2022
DOI: 10.1134/s0036024422070251
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemicals As a Potential Inhibitor of COVID-19: An In-Silico Perspective

Abstract: The current research has centered on the use of pharmacological and binding affinity methods to test the 36 compounds as bioactive constituents’ inhibitors for COVID-19. Six compounds out of 36 phytoconstituents (rutin, quercetin, catechin gallate, rhamnetin, campesterol and stigmasterol) have demonstrated outstanding molecular docking and drug-like properties as HIV inhibitors Lopinavir and Indinavir. Interestingly, the lowest binding energies (LBE) and the inhibition constant ( K i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…It also exhibited potential antiviral behaviour against human immune-deficiency virus (Ong and Khoo 1997 ) Linolenic acid Linolenic acid showed anti-hepatitis B properties in vitro using Hep G2 2.2.15 cell line (Chou et al 2012 ) Pseudocarpaine Pseudocarpaine showed strong binding affinity for receptor binding domain (RBD)-spike protein of SARS-CoV-2 in silico (Adel et al 2022 ) Isorhamnetin Isorhamnetin exhibited inhibitory properties against the main protease of SARS-CoV-2 in silico (Shahhamzehei et al 2022 ) Oleic acid Oleic acid showed anti-inflammatory bactericidal and fungicidal property (Sales-Campos et al 2013 ) Riboflavin Riboflavin demonstrated antiviral activity by significantly lowering Middle-East respiratory syndrome coronavirus titer in the presence of ultraviolet light (Keflie and Biesalski 2021 ) Chlorogenic acid Chlorogenic acid inhibited Influenza A (H5N1) virus neuraminidase activity (Luo et al 2011 ) Coniferol Coniferol exhibited anti-hepatitis B virus activity (Aguilar-Guadarrama and Rios 2018 ) Beta-carotene Beta-carotene was reported to enhance the immunity against virus and tumor surveillance (Fatima et al 2014 ) Campesterol Campesterol showed anti-HIV property. It exhibited inhibitory properties against SARS-CoV-2 in silico (Jamhour et al 2022 ) β-sitosterol β-sitosterol showed inhibitory properties against SARS-CoV-2 in silico (Khan and Siddiqui 2020 ) Myristic acid Myristic acid and its derivatives exhibited inhibitory properties against human immunodeficiency virus and hepatitis B virus in vitro (Parang et al 1997 ) Pentadecylic acid Pentadecylic acid showed antioxidant, anti-inflammatory and anticancer properties (Sharma et al 2014 ) Ferulic acid Ferulic acid showed ...…”
Section: Resultsmentioning
confidence: 99%
“…It also exhibited potential antiviral behaviour against human immune-deficiency virus (Ong and Khoo 1997 ) Linolenic acid Linolenic acid showed anti-hepatitis B properties in vitro using Hep G2 2.2.15 cell line (Chou et al 2012 ) Pseudocarpaine Pseudocarpaine showed strong binding affinity for receptor binding domain (RBD)-spike protein of SARS-CoV-2 in silico (Adel et al 2022 ) Isorhamnetin Isorhamnetin exhibited inhibitory properties against the main protease of SARS-CoV-2 in silico (Shahhamzehei et al 2022 ) Oleic acid Oleic acid showed anti-inflammatory bactericidal and fungicidal property (Sales-Campos et al 2013 ) Riboflavin Riboflavin demonstrated antiviral activity by significantly lowering Middle-East respiratory syndrome coronavirus titer in the presence of ultraviolet light (Keflie and Biesalski 2021 ) Chlorogenic acid Chlorogenic acid inhibited Influenza A (H5N1) virus neuraminidase activity (Luo et al 2011 ) Coniferol Coniferol exhibited anti-hepatitis B virus activity (Aguilar-Guadarrama and Rios 2018 ) Beta-carotene Beta-carotene was reported to enhance the immunity against virus and tumor surveillance (Fatima et al 2014 ) Campesterol Campesterol showed anti-HIV property. It exhibited inhibitory properties against SARS-CoV-2 in silico (Jamhour et al 2022 ) β-sitosterol β-sitosterol showed inhibitory properties against SARS-CoV-2 in silico (Khan and Siddiqui 2020 ) Myristic acid Myristic acid and its derivatives exhibited inhibitory properties against human immunodeficiency virus and hepatitis B virus in vitro (Parang et al 1997 ) Pentadecylic acid Pentadecylic acid showed antioxidant, anti-inflammatory and anticancer properties (Sharma et al 2014 ) Ferulic acid Ferulic acid showed ...…”
Section: Resultsmentioning
confidence: 99%
“…When cytokine storm hits, the afflicted victims die. A cytokine storm caused by a coronavirus can be prevented by several naturally occurring polyphenols, such as curcumin, apigenin, resveratrol, and kaempferol [70] , [71] , [72] , [73] , [74] . These findings suggest that edible antimicrobial coatings on fruits can help prevent virus transmission before infection, while also extending the shelf-life of polyphenolic fruits, which are vital for the recovery of COVID-19 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, compounds (Ib), (II), and (III) are reported herein for the first time in khella plants. Previous literature works have shown the antiviral potential of phytosterols such as β-sitosterol, stigmasterol, and their derivatives against a variety of human viruses [32][33][34][35][36][37]. Likewise, the natural furanocoumarin derivatives, khellin and visnagin have been also reported to possess antiviral properties against some mammalian viruses, e.g.…”
Section: Phytochemical Study Of a Visnaga Rootsmentioning
confidence: 99%